2013
DOI: 10.1084/jem.20122609
|View full text |Cite
|
Sign up to set email alerts
|

In vivo fate mapping identifies pre-TCRα expression as an intra- and extrathymic, but not prethymic, marker of T lymphopoiesis

Abstract: A novel pre-TCRα (pTα) reporter mouse reveals that expression of pTα is confined to the T lineage and does not occur on prethymic progenitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 67 publications
(118 reference statements)
1
24
0
Order By: Relevance
“…Erk2 was conditionally ablated in T lineage progenitors using Ptcra-Cre (Luche et al, 2013), while Erk1 was ablated in the germline (Fischer et al, 2005). Ptcra-Cre mediated ablation of Erk2 began in DN3 (CD4 − CD8 − CD44 − CD25 + ) thymocytes and was complete in DN4 (CD4 − CD8 − CD44 − CD25 − ) and γδTCR + thymocytes (Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
“…Erk2 was conditionally ablated in T lineage progenitors using Ptcra-Cre (Luche et al, 2013), while Erk1 was ablated in the germline (Fischer et al, 2005). Ptcra-Cre mediated ablation of Erk2 began in DN3 (CD4 − CD8 − CD44 − CD25 + ) thymocytes and was complete in DN4 (CD4 − CD8 − CD44 − CD25 − ) and γδTCR + thymocytes (Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with recent fate mapping experiments. 11,12,16 Liberation of niches occupied by tDCs generates a permissive state for T-lineage progenitors to adopt an alternative fate, although the extent to which this alternative pathway of DC development operates in different physiological scenarios remains to be investigated. Of note, the presence of immunoglobulin gene rearrangements exclusively in thymic but not in other cDC subsets suggests, at least in some instances, that tDCs might be generated through this alternative pathway.…”
Section: Discussionmentioning
confidence: 99%
“…11 Consistently, fate mapping based on Ptcra expression showed that tDCs were not derived from T-lineage committed cells. 12 An intrathymic DC progenitor population that is likely to be of independent origin from ETPs was identified in mice expressing a CD207(Langerin)-green fluorescent protein (GFP) reporter gene. 13 In addition, these progenitors already expressed CD11c and low levels of MHC-II, and appeared therefore to be more mature than peripheral pre-DCs of the canonical DC developmental pathway.…”
Section: Introductionmentioning
confidence: 99%
“…MyrAkt2 Tg were generated as previously described using a proximal Lck promoter to restrict expression to T lineage progenitors (18). Conditional ablation of the Pten locus in T lineage progenitors was accomplished by crossing Pten flox/flox mice (19) with those expressing Cre in T lineage progenitors only, under control of the pre-Tα promoter (14). Upon crossing MyrAkt2 Tg or PTEN-deficient mice to Rpl22 −/− mice, littermates on a mixed 129-C57BL/6 background were monitored weekly for signs of disease, as described (2).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Gutierrez et al reported alterations of the PTEN-PI3K-Akt pathway in nearly 50% of pediatric T-ALL (12). The two models used were a MyrAkt2 Tg mouse, in which MyrAkt2 is expressed in T lineage progenitors under the control of a proximal Lck promoter (13) and a conditional knockout mouse where the Pten tumor suppressor gene is ablated in T cell precursors using pre-Tα-Cre (14). Interestingly, both enforced expression of MyrAkt2 and biallelic loss of Pten resulted in a partial rescue of the block in T cell development caused by Rpl22-deficiency.…”
Section: Introductionmentioning
confidence: 99%